2019
DOI: 10.1080/15476286.2019.1574163
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA414c affects salt tolerance of cotton by regulating reactive oxygen species metabolism under salinity stress

Abstract: Salinity stress is a major abiotic stress affecting the productivity and fiber quality of cotton. Although reactive oxygen species (ROS) play critical roles in plant stress responses, their complex molecular regulatory mechanism under salinity stress is largely unknown in cotton, especially microRNA (miRNA)mediated regulation of superoxide dismutase gene expression. Here, we report that a cotton iron superoxide dismutase gene GhFSD1 and the cotton miRNA ghr-miR414c work together in response to salinity stress.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(24 citation statements)
references
References 64 publications
0
23
1
Order By: Relevance
“…6 ). Another study also showed that Sp-miR396a-5p transcript level in Solanaceae was up-regulated under salt stress, and overexpression of Sp-miR396a-5p in tobacco increased its tolerance to salt stress by enhancing osmoregulation and decreased production of reactive oxygen species [ 27 ]. In this study, we observed that expression of miR396b, miR396f and miR396h increased in sesame with the decrease of their target gene GRF1 at 12 and 24 h after salt stress, indicating that miR396 might have a similar regulatory function in sesame resistance to salt stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 ). Another study also showed that Sp-miR396a-5p transcript level in Solanaceae was up-regulated under salt stress, and overexpression of Sp-miR396a-5p in tobacco increased its tolerance to salt stress by enhancing osmoregulation and decreased production of reactive oxygen species [ 27 ]. In this study, we observed that expression of miR396b, miR396f and miR396h increased in sesame with the decrease of their target gene GRF1 at 12 and 24 h after salt stress, indicating that miR396 might have a similar regulatory function in sesame resistance to salt stress.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, one report found that five miRNAs were involved in salt stress response in Hordeum bulbosum using deep sequencing, and demonstrated their critical roles in better tolerance to salt stress in autopolyploids [ 21 ] . It was also clearly demonstrated that overexpression of some miRNAs or their target genes in some transgenic plants resulted in enhanced resistance to salt stress, such as for gma-miR172c [ 9 ], miR319 [ 22 ], miR393 [ 23 ], miR394 [ 24 ], miR395e [ 25 ], Sp-miR396a-5p [ 26 ], ghr-miR414c [ 27 ] and osa-miR528 [ 28 ]. Currently, all of the evidence indicates the importance of miRNA regulation in plant salt tolerance; however, the function of salt-responsive miRNAs and their target genes in sesame remain unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Salinity stress [108] ghr-miR399 and ghr-156e Salt stress [94] miR319 Abiotic stress signaling [109] ghr-miR5272a Immune response [110] multiple miRNAs Salt stress [111] multiple miRNAs High temperature [112] multiple miRNAs Low and high temperature stress [113] miR156a/d/e, miR167a, miR169, miR397a/b, miR399a, miR535a/b, miR827b, Salt stress [114] Cowpea (Vigna unguiculata) multiple miRNAs Drought stress [115] Date Palm (Phoenix dactylifera) multiple miRNAs Salinity stress [116] Flax ( Linum usitatissimum) miR319, miR390, and miR393 Aluminum stress [117] Foxtail Millet (Setaria italica) multiple miRNAs Drought stress [118] multiple miRNAs Dehydration stress [119] Java waterdropwort (Oenanthe javanica) multiple miRNAs Various abiotic stress [120] Maize (Zea mays) multiple miRNAs Chilling stress [121] multiple miRNAs Heat stress [122] multiple miRNAs Nitrogen stress [123] multiple miRNAs Drought stress [82] multiple miRNAs Cadmium stress [124] multiple miRNAs Phosphate deficiency [125] multiple miRNAs Water logging [126] multiple miRNAs Nitrogen deficiency [127] multiple miRNAs Short term water logging [128] miR160, miR164, miR167, miR168, miR169, miR172, miR169, miR395, miR397, miR398, miR399, miR408, miR528, miR827…”
Section: Micrornas Stress Responses Referencementioning
confidence: 99%
“…Additionally, over-expressing miR399f, miR402, and miR408 in Arabidopsis, Tae-miR408 and Sm-MIR408 in tobacco, and Osa-miR528 in creeping bentgrass increases salinity tolerance (Kim et al, 2010a;Feng et al, 2013;Ma et al, 2015;Baek et al, 2016;Bai et al, 2018;Guo et al, 2018), indicating that these miRNAs enhance plant salt stress adaptation. By contrast, over-expressing miR414c, miR417, and miRNVL5 increases sensitivity to salinity stress (Jung and Kang, 2007;Gao et al, 2016;Wang et al, 2019). Collectively, these results suggest that the agronomic trait of salinity stress tolerance could be enhanced by the manipulation of miRNA or its target.…”
Section: Functions Of Mirna Under Salt Stressmentioning
confidence: 95%